Utility of isocitrate dehydrogenase 1 as a serum protein biomarker for the early detection of non‐small‐cell lung cancer: A multicenter in vitro diagnostic clinical trial. Issue 5 (5th May 2020) - Sun, Nan; Sun, Shouguo; Gao, Yibo; Li, Yuan; Lu, Zhiliang; Yuan, Zuyang; Che, Yun; Huang, Jianbing; Mao, Shuangshuang; Lei, Yuanyuan; Zang, Ruochuan; Li, Ning; et al.
Abstract: We aimed to verify the expression status and diagnostic significance of isocitrate dehydrogenase 1 (IDH1) in non‐small‐cell lung cancer (NSCLC), especially during early stages. Serum IDH1 levels were measured by ELISA. A total of 1223 participants (660 patients with NSCLC, 276 healthy controls [HCs], 95 patients with benign pulmonary conditions [BPCs], 135 patients with other cancers [OCs], and 57 samples with interfering factors) were divided into a training cohort and a validation cohort according to 3 testing centers. The IDH1 concentrations in the NSCLC group were obviously higher than those in the control groups ( P  < .001). Area under the receiver operating characteristic curves (AUCs) for discriminating NSCLC patients from controls (HC, BPC, and OC) were 0.870 and 0.745 (sensitivity, 63.3% and 55.0%; specificity, 86.8% and 86.3%) in the training cohort and validation cohort, respectively. The AUCs for discriminating stage 0‐IA lung cancer patients from HCs were 0.907 and 0.788 (sensitivity, 58.6% and 59.1%; specificity, 92.9% and 89.3%) in 2 cohorts, respectively. Isocitrate dehydrogenase 1 showed specificity for NSCLC and had no diagnostic value for other common cancers. Furthermore, IDH1 was significantly reduced in postoperative serum. Isocitrate dehydrogenase 1 shows clinical utility as a serum protein biomarker for the early diagnosis of NSCLC. Abstract : This is the first large‐scale study aiming to verify the level and diagnostic value of serum isocitrate dehydrogenase 1 (IDH1) in non‐small‐cell lung cancer (NSCLC) with well‐designed controls in multicenter‐based cohorts. IDH1 showed high diagnostic efficiency in early stage NSCLC and high specificity for NSCLC comparing to other cancers.